Students' Critical Thinking Skills in Solving Probability - Imam Muqimil Haq; Fika Widya Sawitri (Indo-MathEdu Intellectuals Journal, 2021)
Critical thinking is thinking quickly and rationally in response to the surrounding environment so that it can solve problems well and bring benefits. This research aims to find out the critical thinking skills of students in solving problems on probability. This type of research is qualitative descriptive. The subjects in the study numbered one person who was selected using purposive sampling techniques using the criteria of student test results. The instruments used are tests and interviews. Tests are used to find out students' learning outcomes and interviews are used to determine students' critical thinking skills. Data analysis used is qualitative data analysis consisting of data reduction, data presentation, and conclusion withdrawal. Data analysis results obtained that the subject in the learning process and problem solving process has the ability to think critically and meets three indicators of critical thinking skills, namely trying to know information well, providing reasons for problem solving, and finding alternative solutions.